Research of the Calculation Method of Bending Strength of Non-orthogonal Helical Face Gear - Derun Qin; Long Yang; Jinyuan Tang; Siyu Chen (Jixie chuandong)
There is no analytical calculation method and formula for the calculation of the bending strength of the face gear.For this reason，based on the principle of tooth surface contact analysis，the formula for calculating the length of the bending arm is derived，reference the calculation standard （ISO 10300（3）：2014） of bevel gear bending strength，an analytical calculation method for the root bending strength of non-orthogonal helical face gear is proposed.Taking a parameter face gear transmission pair as an example，the Abaqus finite element software is used to calculate the root bending strength，and the root bending stress value of the non-orthogonal helical face gear is extracted.The finite element results are compared with the analytical calculation results，the error is about 8.5%.The results show that the calculation method of the calculation method of the root bending stress of non-orthogonal helical face gears is correct and feasible.The problem that the calculation of the bending strength of the face gear has no analytical formula is solved.After refinement and perfection，it is expected to form a basic calculation formula for the bending strength design of the face gear.